2015
DOI: 10.1103/physrevd.91.123011
|View full text |Cite
|
Sign up to set email alerts
|

Empirical covariance modeling for 21 cm power spectrum estimation: A method demonstration and new limits from early Murchison Widefield Array 128-tile data

Abstract: The separation of the faint cosmological background signal from bright astrophysical foregrounds remains one of the most daunting challenges of mapping the high-redshift intergalactic medium with the redshifted 21 cm line of neutral hydrogen. Advances in mapping and modeling of diffuse and point source foregrounds have improved subtraction accuracy, but no subtraction scheme is perfect. Precisely quantifying the errors and error correlations due to missubtracted foregrounds allows for both the rigorous analysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 71 publications
4
102
0
Order By: Relevance
“…We found that a small buffer beyond the horizon was necessary to completely mask out the wedge, consistent with Dillon et al (2015a). We implement the buffer by increasing the slope of the horizon line by 14%.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…We found that a small buffer beyond the horizon was necessary to completely mask out the wedge, consistent with Dillon et al (2015a). We implement the buffer by increasing the slope of the horizon line by 14%.…”
Section: Resultssupporting
confidence: 75%
“…The best result from this analysis is an upper limit on the power spectrum of  D2.7 10 2 4 mK 2 at = k h 0.27 Mpc −1 and z = 7.1. This is a modest improvement over the previous best MWA results (Dillon et al 2015a), which is not surprising-given that this integration contains about 10times more data, but is systematics limited. Our results are also consistent with the 40 hr GMRT limit of  D6.15 10 2 4 mK 2 at = k h 0.5 Mpc −1 and z = 8.6 (Paciga et al 2013), though they probe significantly different periods of the EoR.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this paper we present 3 hr of tracking analysis of the EoR1 field centered at R.A.=4 h , decl.=−27°. Many research groups are currently developing pipelines to extract statistical information from radio interferometric data, with an aim to detect the H I signal from EoR (Dillon et al 2015;Jacobs et al 2016;Trott et al 2016; B. J. Hazelton et al 2016, in prepration).…”
Section: Analysis Of Mwa Datamentioning
confidence: 99%
“…The image based pipelines (Dillon et al 2015; B. J. Hazelton et al 2016, in prepration) use a source catalog created through the deconvolution of the data which are subtracted to obtain a residual image cube.…”
Section: Analysis Of Mwa Datamentioning
confidence: 99%